A review of topically administered mini‐tablets for drug delivery to the anterior segment of the eye. (25th August 2013) - Moosa, Raeesa M.; Choonara, Yahya E.; du, Lisa C.; Kumar, Pradeep; Carmichael, Trevor; Tomar, Lomas Kumar; Tyagi, Charu; Pillay, Viness
Abstract Objectives The human eye is a unique and intricate structure which has made drug delivery to the eye a formidable undertaking. Anterior‐segment eye diseases are ubiquitous, especially among elderly patients, and conventional eye drops, although a first‐choice dosage form, are not always an efficient treatment option. The development of novel drug delivery systems for improved treatment is therefore imperative. Key findings In an attempt to circumvent the obstacles presented by the structure of the eye, advanced systems such as ocular mini‐tablets have been developed. In this review, a concerted effort has been made to provide a detailed overview of topically administered ocular mini‐tablets and other solid devices for drug delivery to the anterior segment of the eye. These mini‐tablets have been shown in vitro and in vivo to have significant advantages in comparison with liquid preparations. This is a step toward attaining better patient convenience and compliance, which are critical factors. Summary Solid ophthalmic dosage forms have several advantages that can contribute to assisting with patient compliance and, ultimately, effective disease treatment. In addition to the challenges associated with topical ocular drug delivery, the shortcomings of conventional eye drops, advantages of mini‐tablets, and improvements to date to these systems are discussed. The requirement for further advancements in the ocular field is also emphasized.